2019
DOI: 10.1007/jhep10(2019)031
|View full text |Cite
|
Sign up to set email alerts
|

Transverse momentum dependent distributions in e+e− and semi-inclusive deep-inelastic scattering using jets

Abstract: The extraction of transverse momentum dependent distributions (TMDs) in semiinclusive deep inelastic scattering (SIDIS) is complicated by the presence of both initial-and final-state nonperturbative physics. We recently proposed measuring jets (instead of hadrons) as a solution, showing that for the Winner-Take-All jet axis the same factorization formulae valid for hadrons applied to jets of arbitrary size. This amounts to simply replacing TMD fragmentation functions by our TMD jet functions. In this paper we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 111 publications
(198 reference statements)
3
58
0
Order By: Relevance
“…Because of the factorization theorem, the TMDs have several universal features like rapidity and renormalization scale evolution, which should be also tested including their (universal) non-perturbative part. Recently some of us have considered the possibility to define a jet-TMD, replacing a final state hadron with a jet [6][7][8] in SIDIS and e + e − processes. The check of this possibility has revealed that standard jet definitions are compatible with a factorization theorem only in the case of small enough radii, which is a not obvious experimental condition in the planned electron-hadron collider like EIC or LHeC.…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the factorization theorem, the TMDs have several universal features like rapidity and renormalization scale evolution, which should be also tested including their (universal) non-perturbative part. Recently some of us have considered the possibility to define a jet-TMD, replacing a final state hadron with a jet [6][7][8] in SIDIS and e + e − processes. The check of this possibility has revealed that standard jet definitions are compatible with a factorization theorem only in the case of small enough radii, which is a not obvious experimental condition in the planned electron-hadron collider like EIC or LHeC.…”
Section: Contentsmentioning
confidence: 99%
“…Instead large jet-radii need a specific definition of jet, which allows soft radiation to be independent of radius. In [7,8] this was achieved using the winner-take-all (WTA) axis [9], and the perturbative calculations were done with a precision similar to the case of fragmenting hadrons.…”
Section: Contentsmentioning
confidence: 99%
“…However, in certain regions of phase space, the transverse momenta of the partons become relevant, and one needs the transverse momentum dependent PDFs (TMDPDFs) and FFs (TMDFFs) in the corresponding factorization formulas. This is case for the small transverse momentum (Q T ) region in the Drell-Yan process [3][4][5][6][7][8][9][10][11], and also for similar regions in, e.g., semi-inclusive deep-inelastic scattering (SIDIS) [12][13][14][15][16], electron-positron annihilation to hadrons and jets [17][18][19][20][21][22], Higgs boson production [23][24][25][26][27][28][29][30], top quark pair production [31][32][33][34], as well as Energy-Energy Correlator (EEC) in the back-to-back limit at both lepton and hadron colliders [35,36]. To improve the theoretical predictions for these observables, it is desirable to have precise knowledges about these basic objects.…”
Section: Introductionmentioning
confidence: 96%
“…Analytical calculations, phenomenological applications, and experimental determinations of the TMD distributions play important role in understanding the structure of hadrons [1,2]. TMDPDFs and TMDFFs have important applications in collider processes, such as Drell-Yan [3][4][5][6][7][8][9][10][11] and Higgs production [12][13][14][15][16][17][18][19], top quark pair production [20][21][22][23], hadronic J/ψ production, semi-inclusive deep-inelastic scattering [24][25][26][27][28], hadron or jet production in electron-positron annihilation [29][30][31][32][33][34], and energy correlators in both e + e − and hadron colliders [29,35,36]. The TMDPDFs and TMDFFs are intrinsically non-perturbative objects.…”
Section: Introductionmentioning
confidence: 99%